Investigation of Phytoplankton and Physico-chemical Parameters in Nursery, Growout and Broodstock Ponds - Hossain, M. I.; Alam, M. M.; Alam, M.; Kamal, B. M. M.; Galib, S. M. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> <![endif]--> The study measures the relationship between physico-chemical variables with the cell density of phytoplankton in nursery, growout and broodstock ponds of fish. This study was conducted at Natore Government Fish Farm in Bangladesh from January to June, 2012. The observed physico-chemical variables like water temperature, transparency, dissolved oxygen, pH, ammonia-nitrogen, total alkalinity and total hardness were found within the standard ranges. Phytoplankton belonging to bacillariophyceae, chlorophyceae, cyanophyceae and euglenophyceae were found among the ponds but euglenophyceae with highest abundance was recorded in almost all the ponds. Total abundance of different groups of phytoplankton was recorded as mean (±SD) cell density (cell/l) (62.77±2.16)×104, (47.22±0.69)×104, and (77.12±3.42)×104 in nursery pond, growout pond and broodstock pond, respectively. Overall phytoplankton abundance was more in broodstock pond than in others. Total phytoplankton density has exhibited significantly positive correlation with dissolved oxygen (DO) and inverse relation with water temperature, pH, ammonia-nitrogen and total alkalinity in case of nursery pond. For growout pond, total phytoplankton density has exhibited significantly positive correlation with temperature and transparency, and significantly negative correlation with other physico-chemical characteristics. In case of broodstock pond, total phytoplankton density has no significant relationship with any physico-chemical variables of water. Keywords: Nursery pond; Growout pond; Broodstock pond; Phytoplankton; Water quality, physico-chemical parameters © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.14886 J. Sci. Res. 5 (3), 555-571 (2013) <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->